Contextual Determinants of Learning Behaviour Differentials amongst Host-farmers of University-Student Outreach in Uganda - Kalule, Stephen W.; Sseguya, Haroon; Ongeng, Duncan; Karubanga, Gabriel A. (Advances in Agricultural Science, 2019)
In Sub-Saharan Africa, a knowledge void still exists on two contextual questions of university-community outreach: 1) how social demographics differences are related to farmer learning behaviour towards student outreach, and 2) how student outreach models compare with public and non-public extension services. A cross-section survey was used to obtain data from a sample of 283 respondents purposively selected from previous hosts of student outreach of Gulu University in Uganda. Results from Kruskal-Wallis method revealed that there were significant differences among host-farmers with respect to farmstead distance to the university for knowledge sharing (?2 (2) = 8.5; P < 0.05) and giving feedback (?2 (2) = 7.6; P < 0.05). Regarding the experience of participating in outreach program, significant differences among host-farmers were found in seeking information (?2 (2) = 12.3; P < 0.01); knowledge sharing (?2 (2) = 10.4; P < 0.01); seeking feedback (?2 (2) = 16.4; P < 0.01) and giving feedback (?2 (2) = 8.1; P < 0.05). Further, Friedman test results showed that host-farmers perceived the university-student outreach to be superior and significantly different from public and non-public agricultural extension. We conclude that university outreach is a useful service to farmer. However, its success in facilitating farmer learning is dependent on farmstead distance to the university and farmers’ level of experience of participating in university activities. We recommend more logistical support from governments to university outreach programs so that outreach services can efficiently complement public and non-public interventions in delivering community-based training and learning approaches.
Keywords: Higher education, Community linkages, Farmer learning